PNERAPAN STRATEGIEXPERIENTAL LEARNING (BELAJAR PENGALAMAN) DENGAN PRINSIP 4 M UNTUK MENINGKATKAN PRESTASI BELAJAR IPA - Ni Ketut Soka (Jurnal Santiaji Pendidikan (JSP), 2018)
This research was conducted at SD Negeri 15 Pemecutan in fourth grade whose students' ability to understand the learning achievement of science was low. The aim of this classroom action research is to find out whether experiential learning strategy by using 4 M principles can improve the students’ achievement in learning science.The method of data collection is the science achievement test. The method of data analysis is descriptive. The result obtained from this research is experiental learning strategy by using 4 M principles can improve students’ science learning achievement. This evident showed on the results obtained initially 62.10, in the first cycle to 76.00 and in the second cycle to 77.12. The conclusion obtained of this research is experiental learning strategy by using 4 M principles can improve students’ science learning achievement.